Relationships between habitats, forages and carrying capacity of moose range in Northern Alberta Part 1: Moose preferences for habitat and strata and forages ... - Nowlin, R. A. (University of Alberta Library, 1978)
Relationships between moose (Alces alces andersoni) and the habitat strata and forages available to them in northern Alberta were studied within the Alberta Oil Sands Environmental Research Program (AOSERP) study area during fall (September through November 1976) and winter (December 1976 through March 1977). Radio telemetry was employed to delineate seasonal use, and preference and avoidance of both habitat strata and forages. Specific categories of use of habitats were also identified and evaluated. These included feeding, bedding, non-feeding-bedding, and "presence only". In addition, environmental variables affecting habitat use were variously identified and measured. Both physical and vegetation variables were considered. The habitat use data indicated that upland habitat strata were most heavily utilized and were preferred (p<0.01), whiIe lowlands were least utiIized and were avoided (p<0.01), during both fall and winter, for all categories of habitat use except non-feeding-bedding. Individual ...